A better use of fertilizers is needed for global food security and environmental sustainability - Penuelas, Josep; Coello, Fernando; Sardans, Jordi (Agriculture & food security, 2023)
The massive use of fertilizers during the last decades allowed a great increase in the global capacity of food production. However, in the last years, several studies highlight the inefficiency and country asymmetries in the use of these fertilizers that generated environmental problems, soil nutritional imbalances and not optimal food production. We have aimed to summarize this information and identify and disentangle the key caveats that should be solved. Inadequate global management of fertilization produces areas with serious nutrient deficits in croplands linked with insufficient access to fertilizers that clearly limit food production, and areas that are overfertilized with the consequent problems of environmental pollution affecting human health. A more efficient use of nitrogen (N), phosphorus (P) and potassium (K) fertilizers for food security while preserving the environment is thus needed. Nutrient imbalances, particularly the disequilibrium of the N:P ratio due to the unbalanced release of N and P from anthropogenic activities, mainly by crop fertilization and expanding N-fixing crops that have continuously increased the soil N:P ratio, is another issue to resolve. This imbalance has already affected several terrestrial and aquatic ecosystems, altering their species composition and functionality and threatening global biodiversity. The different economic and geopolitical traits of these three main macronutrient fertilizers must be considered. P has the fewest reserves, depending mostly on mineable efforts, with most of the reserves concentrated in very few countries (85% in Morocco). This problem is a great concern for the current and near-future access to P for low-income countries. N is instead readily available due to the well-established and relatively low-cost Haber–Bosch synthesis of ammonium from atmospheric N 2 , which is increasingly used, even in some low-income countries producing an increasing imbalance in nutrient ratios with the application of P and K fertilizers. The anthropogenic inputs of these three macronutrients to the environment have reached the levels of the natural fluxes, thereby substantially altering their global cycles. The case of the excess of N fertilization is especially paradigmatic in several areas of the world, where continental water sources have become useless due to the higher nitrate concentrations. The management of N, P and K fertilizers is thus in the center of the main dichotomy between food security and environmentally driven problems, such as climate change or eutrophication/pollution. Such a key role demands new legislation for adopting the well-known and common-sense 4R principle (right nutrient source at the right rate, right time and right place) that would help to ensure the appropriate use of nutrient resources and the optimization of productivity.